A high-rebound sole material and preparation method thereof
By adding polytetrafluoroethylene microporous fibers and high elastic particles to the EVA sole material, the problem of rebound loss and permanent deformation of EVA sole material after long-term wear is solved, achieving higher elastic recovery rate and wear resistance.
Patent Information
- Application Number
- CN202411739377.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
AI Technical Summary
The existing EVA sole materials have a large rebound loss after long-term wear, which is prone to permanent deformation and degradation of mechanical properties.
EVA matrix resin is used as the main raw material, and polytetrafluoroethylene microporous fibers and high-elastic particles are incorporated. The high-elastic particles are composed of TPU layer, mixed layer and TPU layer. They are prepared by casting and vacuum drying, which increases the elastic recovery rate and wear resistance of the material.
It improves the elastic recovery rate of sole material, reduces permanent deformation, enhances the wear resistance and stability of the material, and extends the service life.
Smart Images

Figure BDA0005162273590000091 
Figure BDA0005162273590000111 
Figure BDA0005162273590000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and more specifically, to a high-resilience sole material and a preparation method thereof. Background Art
[0002] Shoes are something we wear every day, and the soles are an indispensable part of making shoes. With the improvement of living standards, people's requirements for footwear and daily necessities are getting higher and higher, and more and more attention is paid to the quality and comfort of the soles. Ethylene-vinyl acetate copolymer (EVA) is made by copolymerization of ethylene (E) and vinyl acetate (VA). Foamed EVA is currently the main material for soles, especially for sports shoes. It has the advantages of light weight, softness, and comfort. The rebound performance is generally 45%. With the continuous research and development and exploration of chemical sole factories on the application of EVA materials, various brands have gradually launched some EVA soles with high rebound performance.
[0003] In the prior art, the Chinese invention patent application document with application number CN202010631780.5 discloses a high-resilience and wear-resistant sole material and a preparation method thereof. The sole material comprises the following components by weight: 18-23 parts of POE; 45-65 parts of EVA; 4.5-7.5 parts of filler; 3.5-6.5 parts of wear-resistant agent; 1-2 parts of zinc stearate; 1-2 parts of zinc oxide; 0.5-1.2 parts of stearic acid; 0.1-0.5 parts of bridging agent; 0.5-1.2 parts of hydrocarbon resin; 1.5-3.5 parts of foaming agent; 0.5-1.0 parts of cross-linking agent; EVA includes 20-30 parts of a first EVA, 10-18 parts of a second EVA and 15-25 parts of a third EVA.
[0004] The rebound rate of the above-mentioned sole material reaches 58-60%, and it can maintain high resilience and wear resistance at the same time. Compared with traditional soles, it is lighter, more comfortable to wear, and can relieve foot fatigue. However, after long-term wearing, the EVA sole material with a high foaming ratio loses a lot of resilience, is prone to permanent deformation, and has a serious decline in mechanical properties. Summary of the invention
[0005] In order to improve the resilience of EVA sole materials, reduce the resilience loss after wearing, and reduce the permanent compression deformation, the present application provides a high-rebound sole material and a preparation method thereof.
[0006] In a first aspect, the present application provides a high-resilience sole material, which adopts the following technical solution: A high-resilience sole material comprises the following raw materials in parts by weight: 100 parts of EVA base resin, 1-3 parts of stearic acid, 8-12 parts of foaming agent, 5-10 parts of cross-linking agent, 10-20 parts of inorganic filler, 5-10 parts of cell stabilizer, 5-10 parts of polytetrafluoroethylene microporous fiber, and 10-15 parts of high-elastic particles; The highly elastic particles include a TPU layer, a mixed layer and a TPU layer in contact with each other, the TPU layer is cast by a TPU solution, the mixed layer is cast by a mixed solution formed by left-handed polylactic acid and modified graphene oxide, the mass ratio of left-handed polylactic acid to modified graphene oxide in the mixed solution is 1:0.03-0.05, and the mass ratio of the casting amount of TPU solution to the casting amount of the mixed solution in a single TPU layer is 1:0.6-0.8.
[0007] By adopting the above technical scheme, EVA matrix resin is used as the main raw material, and an appropriate amount of polytetrafluoroethylene microporous fibers and high-elastic particles are added. The polytetrafluoroethylene in the polytetrafluoroethylene microporous fibers is a low-surface energy material with excellent performance, and the microporous fibers have a mesh structure formed by connecting fine fibers. These fine structures form countless micropores inside the material, which enables it to undergo a large deformation when subjected to force, thereby showing good elasticity; the high-elastic particles made of TPU layer, left-handed polylactic acid layer and TPU layer have good elastic recovery rate, and polyurethane is a polymer formed by the chemical reaction of isocyanate and a compound having active hydrogen such as hydroxyl group. It has both the elasticity of rubber and excellent processing performance, and has a certain cross-linking network, which can provide good resilience. The invention discloses a reversible phase, a polyurethane with elastomeric properties as the fixed phase, and a dual-continuous phase structure prepared by layer-by-layer assembly technology to obtain a high-elastic material with a sandwich structure, thereby improving the high elasticity and high elastic recovery rate of the sole material; the interface compatibility of L-polylactic acid and polyurethane is good, which ensures that the two components can effectively transfer force through the interface, so that the material has an excellent shape recovery rate, and the molecular chains at the interface of the TPU layer and the mixed layer penetrate each other, so that the TPU layer and the mixed layer are firmly combined together and force is transferred to each other through the interface. The mixed layer containing L-polylactic acid is sandwiched by two TPU layers. When recovery deformation occurs, the elastic recovery provided by TPU can act on the two layers of the mixed layer, so that it has a better shape recovery effect, thereby improving the elastic recovery rate of the sole material and reducing permanent deformation.
[0008] Optionally, the preparation method of the highly elastic particles is as follows: Dissolving a thermoplastic polyurethane elastomer to prepare a TPU solution having a concentration of 10-12 wt %; Dissolving L-polylactic acid to obtain a solution with a concentration of 15-18 wt%, adding modified graphene oxide, heating to 80-90° C. and stirring evenly to obtain a mixed solution; The TPU solution is poured into a mold, vacuum dried to obtain a TPU layer, the mixed liquid is poured on the TPU layer, vacuum dried to form a mixed layer, and the TPU solution is poured on the mixed layer, vacuum dried to form a TPU layer, hot pressed into thin sheets, and crushed to obtain high-elastic particles.
[0009] By adopting the above technical scheme, L-polylactic acid is used as the reversible phase, an elastomeric polyurethane with a physical cross-linking network is used as the fixed phase, and two TPU layers and a mixed layer in the middle are used to prepare high-elastic particles. The polyurethane phase always maintains an elastic state. During the compression and rebound process of the sole, it plays the role of a fixed phase to record the initial shape and provide a stable restoring force during the deformation of the sole. The polyurethane with elastomeric properties can provide a certain restoring driving force for the mixed layer formed by polylactic acid. However, L-polylactic acid is a random compound and has a crystal network as a hard segment of shape memory. The material itself does not have There is no physical or chemical cross-linking network, and its own shape recovery performance is poor. Therefore, modified graphene oxide is added to it, and the graphene network is constructed by casting. A high-strength inorganic network is added to the original hard segment network. The addition of modified graphene oxide can connect more tightly with polylactic acid, with less void structure and increased wear resistance. Modified graphene oxide acts as an elastic element during the deformation process of the mixed layer, which can not only reduce the viscous flow of polymer chains, but also store more energy during the deformation process, and the energy dissipated by converting into heat energy is reduced, which is beneficial to shape recovery, thereby improving the elastic recovery rate.
[0010] Optionally, the modified graphene oxide is reduced-modified graphene oxide grafted with polycaprolactone.
[0011] By adopting the above technical scheme, polycaprolactone is grafted on the reduced modified graphene oxide, which can improve the dispersibility of the modified graphene oxide in chloroform and prevent the agglomeration of graphene sheets. In addition, the grafting of polycaprolactone improves the compatibility of the reduced modified graphene oxide with L-polylactic acid, and plays a toughening role on the L-polylactic acid. Polycaprolactone avoids the appearance of gaps between graphene and L-polylactic acid through the entanglement with L-polylactic acid, and at the same time strengthens the interfacial force between the two, which is beneficial to tensile deformation, improves elasticity, and enhances stress transfer during the recovery process. The reduced modified graphene oxide grafted PCL and L-polylactic acid base The good bulk interface bonding is beneficial to stress transfer, which helps the reduced modified graphene oxide to strengthen the L-polylactic acid, increase the tensile strength and elongation at break, and make the formed mixed layer have good load transfer; and the good dispersion of the reduced modified graphene oxide grafted polycaprolactone in the L-polylactic acid promotes nucleation, improves the crystallization ability of the L-polylactic acid, thereby improving the thermal stability, so that the mixed layer in the high-elastic particles has better stability during mixing, and improves the high-temperature modulus and shape recovery force. On the other hand, the graphene network, as a hard segment of shape memory, stores more energy during the deformation process and significantly improves the shape recovery rate.
[0012] Optionally, the polytetrafluoroethylene microporous fiber is made by mixing a polyethylene oxide solution and a polytetrafluoroethylene emulsion, electrospinning, and sintering at 400-420° C. for 5-10 minutes, and the mass ratio of polyethylene oxide to polytetrafluoroethylene is 0.03-0.05:1.
[0013] By adopting the above technical scheme, polyethylene oxide is a high molecular polymer with good water solubility, which can be used as a sacrificial material for the electrostatic spinning of polytetrafluoroethylene fibers. The spinning aid polyethylene oxide is wrapped in the polytetrafluoroethylene microspheres to form fibers with a granular surface. Because the decomposition temperature of polyethylene oxide is about 400°C, the polyethylene oxide is removed by sintering, and the high temperature can melt the polytetrafluoroethylene microspheres to form pure polytetrafluoroethylene microporous fibers. The low surface energy and the micro-nano rough structure of the surface help to improve the hydrophobic properties of the fiber surface, and can improve the dispersibility of the polytetrafluoroethylene microporous fibers in the sole material. After the polyethylene oxide is removed by sintering, the polytetrafluoroethylene fiber presents a microporous structure, thereby improving its rebound rate.
[0014] Optionally, the inorganic filler is carbon nanotube / PCL composite fiber.
[0015] By adopting the above technical solution and using the composite fibers obtained by carbon nanotubes and PCL as fillers, the tensile strength, wear resistance and resilience of the sole material can be effectively improved, and its elastic deformation can be reduced.
[0016] Optionally, the carbon nanotube / PCL composite fiber is prepared as follows: EVA resin and PCL resin were mixed in a mass ratio of 0.2-0.3:1 and melted. 60 The fiber matrix is prepared by irradiating with a Co source at a dose of 100-200 kGy and then melt extruding. The fiber matrix is placed in a xylene solution at 40-50° C., soaked for 30-40 minutes, then added into a carbon nanotube dispersion, ultrasonicated, filtered, washed and dried.
[0017] By adopting the above technical scheme, EVA and PCL are blended and irradiated, and the two can be cross-linked to form a cross-linked network structure, and good shape memory performance is obtained. The cross-linked EVA and PCL are hot-melt extruded and spun to obtain a fiber matrix, which is then immersed in a xylene solution. Since xylene diffuses into the fiber matrix, the fiber matrix can produce volume expansion. The swollen fiber matrix is ultrasonically treated in a carbon nanotube dispersion, and the carbon nanotubes adhere to the fiber matrix, so that the surface roughness of the fiber matrix is increased, and the carbon nanotubes are uniformly distributed on the fiber matrix in an embedded or semi-inserted form, so that the carbon nanotubes form a three-dimensional network on the surface of the fiber matrix. The anchoring effect of the embedded structure allows the three-dimensional structure to always maintain the same deformation as the fiber matrix, thereby obtaining a carbon nanotube / PCL composite fiber with excellent shape recovery performance, so that the sole material has excellent stability and outstanding dynamic durability, and the carbon nanotubes are entangled with each other on the surface of the fiber matrix, which improves the mechanical properties of the fiber matrix, so that the composite fiber has a high elastic recovery rate and good tensile resistance and wear resistance.
[0018] Optionally, the carbon nanotube dispersion comprises polyethersulfone-modified carbon nanotubes and polyimide emulsion in a mass ratio of 1:0.5-1.
[0019] By adopting the above technical scheme, carbon nanotubes have excellent mechanical, thermal and electrical properties, but carbon nanotubes are easy to agglomerate, and the surface is chemically inert and has poor dispersibility. It is easy to produce uneven adhesion on the surface of the fiber matrix and it is difficult to form efficient bonding. Therefore, polyethersulfone is used to modify the carbon nanotubes to improve the dispersibility of the carbon nanotubes. Polyethersulfone will not destroy the ordered graphitized structure of the carbon nanotubes. In addition, a layer of polyethersulfone resin is covalently grafted on the surface of the carbon nanotubes, which reduces the attraction between the carbon nanotubes and greatly improves the dispersibility of the carbon nanotubes in the polyimide emulsion. The bonding force between the carbon nanotubes and the polyimide is enhanced. In addition, the bonding property of the polyimide is used to firmly adhere the polyethersulfone-modified carbon nanotubes to the fiber matrix. In addition, the carbon nanotubes form bridges between adjacent polyimides and form Three-dimensional network structure, polyethersulfone modified carbon nanotubes can significantly improve the strength and stiffness of the fiber matrix, inhibit the peeling of debris on the wear surface, and improve the wear resistance of the fiber matrix. Polyimide and polyethersulfone modified carbon nanotubes have a synergistic effect, because the carbon nanotubes extending out of the fiber matrix surface and the broken carbon nanotubes form a micro needle bearing between the friction pairs, and the three-dimensional network structure formed by carbon nanotubes and polyimide further improves the stiffness of the fiber matrix and reduces the plastic deformation of the matrix during friction. Moreover, the three-dimensional network structure has a heat conduction effect, which greatly improves the thermal conductivity of the matrix fiber and reduces the temperature of the friction surface, thereby improving the wear reduction and anti-wear effect of the fiber matrix. Polyethersulfone modified carbon nanotubes reduce the stress concentration at the interface between polyimide and the fiber matrix and improve the bearing capacity of the wear surface.
[0020] Optionally, the VA content of the EVA resin is 28-33wt%.
[0021] By adopting the above technical scheme, the presence of ethylene chain segments makes EVA resin have better plasticity and wear resistance, and the increase of VA content increases the number of branches in the EVA molecular structure, making EVA have better flexibility and higher elastic recovery rate. After multiple stretching / relaxation cycles, it can still maintain a high elastic recovery rate, which is more helpful for the stability and durability of the sole material.
[0022] Optionally, the foaming agent is AC foaming agent; the cross-linking agent is dicumyl peroxide; The cell stabilizer is selected from at least one of zinc oxide, zinc stearate, magnesium stearate and zinc carbonate.
[0023] In a second aspect, the present application provides a method for preparing a high-resilience sole material, using the following technical solution: A method for preparing a high-resilience sole material comprises the following steps: The EVA matrix resin, stearic acid, inorganic filler, cell stabilizer, polytetrafluoroethylene microporous fiber and high elastic particles are mixed and kneaded at 115-125° C. for 10-15 minutes to prepare a premix; The premix is mixed with a foaming agent and a cross-linking agent, kneaded at 100-110°C for 5-10 minutes, and then granulated to obtain pellets, which are injected into a mold at an injection temperature of 110-140°C.
[0024] By adopting the above technical scheme, the raw materials except the foaming agent and the cross-linking agent are blended and kneaded to be evenly mixed, granulated after adding the foaming agent and the cross-linking agent, injected into the mold, and injection molded to obtain a sole material with good resilience and not easy to deform.
[0025] In summary, this application has the following beneficial effects: 1. Since the present application adopts EVA matrix resin as the main material, and is mixed with an appropriate amount of polytetrafluoroethylene microporous fibers and high-elastic particles, the high-elastic particles are made of a TPU layer, a mixed layer and a TPU layer cast in sequence, with the TPU layer as the fixed phase, which has high elasticity, so that high-elastic particles with high elasticity, not easy to lose elasticity, and good resistance to permanent deformation can be obtained, which are used to improve the elastic recovery rate of the sole material.
[0026] 2. In the present application, it is preferred to use L-polylactic acid and reduced modified graphene oxide grafted polycaprolactone in the mixed layer. Polycaprolactone can be entangled with L-polylactic acid to avoid the formation of pores between modified graphene oxide and L-polylactic acid, increase the interfacial force between the two, increase tensile strength and elasticity, and improve shape recovery ability.
[0027] 3. In the present application, PCL and EVA are preferably used for melt spinning after radiation crosslinking to obtain a fiber matrix, which is then impregnated with a carbon nanotube dispersion to prepare a carbon nanotube / PCL composite fiber to obtain a composite fiber with excellent shape recovery properties. Moreover, the carbon nanotube dispersion is made of polyethersulfone-modified carbon nanotubes and polyimide emulsion, which can further improve the wear resistance of the fiber matrix. DETAILED DESCRIPTION
[0028] The following examples further illustrate the present application in detail.
[0029] Preparation Example I of Polyethersulfone Modified Carbon Nanotubes: (1) Preparation of Aminated Polyethersulfone: 10 g of polyethersulfone powder was added to 70 ml of a mixed solution of nitric acid and sulfuric acid (V / V=3 / 4), stirred at 60°C for 6 h, cooled and vacuum filtered, rinsed with deionized water for 3 times, and dried at 80°C for 12 h to obtain nitrated polyethersulfone; 20 g of tin chloride and 20 g of hydrochloric acid were dissolved in 50 ml of ethanol, 3 g of nitrated polyethersulfone was added, stirred at 60°C for 4 h, cooled to room temperature, filtered, rinsed with deionized water twice, and dried at 100°C for 24 h. The polyethersulfone powder was selected from BASF of Germany and the brand was E3010; (2) Preparation of oxidized carbon nanotubes: 1 g of multi-walled carbon nanotubes was added to 300 ml of a mixture of nitric acid and sulfuric acid (V / V = 1:3), stirred at 80°C for 2 h, ultrasonically dispersed for 1 h, centrifuged at 5000 rpm for 10 min, the supernatant was poured out, the remaining carbon nanotubes were redispersed in deionized water, ultrasonicated for 10 min, filtered with a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm and repeatedly rinsed until neutral, and dried to obtain oxidized carbon nanotubes. The multi-walled carbon nanotubes were selected from Shandong Dazhan, model GT-300; (3) Preparation of polyethersulfone modified carbon nanotubes: 5 g of oxidized carbon nanotubes were added to 100 ml of dehydrated dimethylformamide and ultrasonicated for 30 min to obtain a carbon nanotube suspension. 5.5 g of amino polyethersulfone, 20 g of N,N-dicyclohexylcarbodiimide and 1.5 g of dimethylaminopyridine were dissolved in 200 ml of DMF in sequence and magnetically stirred for 10 min to obtain a polymer solution. The carbon nanotube suspension and the polymer solution were mixed and stirred for 24 h under a nitrogen atmosphere. After the reaction was completed, the mixture was filtered through a polytetrafluoroethylene membrane with a pore size of 0.2 μm, repeatedly rinsed with deionized water, and then dried at 80°C for 24 h to obtain polyethersulfone modified carbon nanotubes.
[0030] Preparation Example 1-6 of High Elastic Particles In the following preparation examples, the thermoplastic polyurethane elastomer is selected from BASF of Germany, model 1180A, and the L-polylactic acid is selected from Nature Works, brand 3001D, with a density of 1.24 g / cm 3, the melt flow rate (210°C, 2.16kg) is 22g / 10min.
[0031] Preparation Example 1: (1) 12 g of thermoplastic polyurethane elastomer was completely dissolved in DMF at 85° C. to prepare a TPU solution with a concentration of 12 wt %; (2) 18 g of L-polylactic acid was dissolved in chloroform to prepare a solution with a concentration of 18 wt %, 0.9 g of modified graphene oxide was added, and the mixture was heated to 90° C. and stirred for 3 h to obtain a mixed solution, wherein the modified graphene oxide was graphene oxide modified by silane coupling agent KH550; (3) The TPU solution was poured into a mold and vacuum dried at 100°C for 24 hours to obtain a TPU layer, the mixed liquid was poured on the TPU layer, and vacuum dried at 100°C for 24 hours to form a mixed layer, and the TPU solution was poured on the mixed layer again, and vacuum dried at 100°C for 24 hours to form a TPU layer, and the resultant was hot-pressed into 2 mm thin sheets using a flat vulcanizer, and crushed to obtain high-elastic particles with an average particle size of 1 mm. The mass ratio of the poured amount of the mixed liquid to the poured amount of the TPU solution in a single TPU layer was 0.8:1.
[0032] Preparation Example 2: (1) 10 g of thermoplastic polyurethane elastomer was completely dissolved in DMF at 85° C. to prepare a TPU solution with a concentration of 10 wt %; (2) dissolving 15 g of L-polylactic acid in chloroform to prepare a solution with a concentration of 15 wt%, adding 0.45 g of modified graphene oxide, heating to 90° C. and stirring for 3 h to obtain a mixed solution, wherein the modified graphene oxide is graphene oxide modified by silane coupling agent KH550; (3) The TPU solution was poured into a mold and vacuum dried at 100°C for 24 hours to obtain a TPU layer, the mixed liquid was poured on the TPU layer, and vacuum dried at 100°C for 24 hours to form a mixed layer, and the TPU solution was poured on the mixed layer again, and vacuum dried at 100°C for 24 hours to form a TPU layer, and the resultant was hot-pressed into 2 mm thin sheets using a flat vulcanizer, and crushed to obtain high-elastic particles with an average particle size of 1 mm. The mass ratio of the poured amount of the mixed liquid to the poured amount of the TPU solution in a single TPU layer was 0.6:1.
[0033] Preparation Example 3: The difference from Preparation Example 1 is that no modified graphene oxide is added to the mixed solution.
[0034] Preparation Example 4: The difference from Example 1 is that step (3) is: pouring the mixed liquid into a mold, vacuum drying at 100°C for 24 hours to form a mixed layer, then pouring TPU solution on the mixed layer, vacuum drying at 100°C for 24 hours to form a TPU layer, then pouring the mixed liquid on the TPU layer, vacuum drying at 100°C for 24 hours to form a mixed layer, and the mass ratio of the poured amount of mixed liquid to the poured amount of TPU solution in a single TPU layer is 1:0.6.
[0035] Preparation Example 5: The difference from Preparation Example 1 is that no mixing layer is set, and a TPU layer is formed by casting a TPU solution with a concentration of 12wt%, which is hot-pressed into 2mm thin sheets and then crushed to obtain high-elastic particles with an average particle size of 1mm.
[0036] Preparation Example 6: The difference from Preparation Example 1 is that the modified graphene oxide is reduced-modified graphene oxide grafted with polycaprolactone, and the reduced-modified graphene oxide grafted with polycaprolactone is prepared by the following method: 30 mg of graphene oxide and 20 ml of diethylene glycol are mixed, ultrasonically dispersed for 1 hour, stirred at 220° C. for 6 hours under a nitrogen atmosphere, cooled and repeatedly washed with ethanol, and the purified product is dried at 60° C. to constant weight to obtain reduced-modified graphene oxide; 100 mg of reduced modified graphene oxide was added to 20 ml of DMF, ultrasonically treated for 30 min, 0.5 ml of stannous octoate and 3 ml of ε-caprolactone were added, and the mixture was reacted at 120 °C for 24 h under a nitrogen atmosphere. After cooling, the mixture was dissolved with chloroform, precipitated with ethanol, and dried at 30 °C to constant weight.
[0037] Preparation Example 7-14 of Carbon Nanotube / PCL Composite Fiber In the following preparation examples, EVA resin with a VA content of 28% is selected from BASF-Yangzi, model V6110M, EVA resin with a VA content of 33% is selected from Lotte, South Korea, model VA810, EVA resin with a VA content of 18% is selected from Formosa Plastics, Taiwan, China, model 7350M, PCL is selected from Ingevity, USA, brand 6800D, and polyimide emulsion is selected from Dongguan Jingke, brand PI1020.
[0038] Preparation Example 7: EVA resin and 100 g PCL resin were mixed at a mass ratio of 0.3:1, kneaded at 70°C, and then 60 The fiber matrix was prepared by irradiating with a Co source at a dose of 200 kGy for 2 h and then melt extruding. During extrusion, the heating temperatures of the four zones were 85°C, 90°C, 95°C and 100°C, the main screw speed was 40 rpm, the feed screw speed was 30 rpm, the extrusion speed was 2 m / min, the distance from the extrusion die to the collecting roller was 100 cm, and the VA content of the EVA resin was 33%. The fiber matrix was placed in a xylene solution at 40°C, soaked for 40 minutes, then added to a carbon nanotube dispersion, ultrasonicated for 10 minutes, filtered, washed with deionized water, and ventilated and dried for 24 hours. The carbon nanotube dispersion was prepared by dispersing 100 mg of multi-walled carbon nanotubes in a mixture of 20 ml of DMF and 80 ml of deionized water, and ultrasonicated for 10 minutes. The multi-walled carbon nanotubes were selected from Shandong Dazhan, model GT-300.
[0039] Preparation Example 8: EVA resin and 100 g PCL resin were mixed in a mass ratio of 0.2:1, kneaded at 70°C, and then 60 The fiber matrix was obtained by irradiating the fiber with a Co source at a dose of 100 kGy for 4 hours and then melt extruding. During extrusion, the heating temperatures of the four zones were 85°C, 90°C, 95°C and 100°C, the main screw speed was 40 rpm, the feed screw speed was 30 rpm, the extrusion speed was 2 m / min, the distance from the extrusion die to the collecting roller was 100 cm, and the VA content of the EVA resin was 28%. The fiber matrix was placed in a xylene solution at 50°C, soaked for 30 minutes, then added to a carbon nanotube dispersion, ultrasonicated for 10 minutes, filtered, washed with deionized water, and ventilated and dried for 24 hours. The carbon nanotube dispersion was prepared by dispersing 100 mg of multi-walled carbon nanotubes in a mixture of 20 ml of DMF and 80 ml of deionized water, and ultrasonicated for 10 minutes. The multi-walled carbon nanotubes were selected from Shandong Dazhan, model GT-300.
[0040] Preparation Example 9: The difference from Preparation Example 7 is that 60 The EVA resin and PCL were blended in a mass ratio of 0.3:1 and then melt-extruded to obtain a fiber matrix.
[0041] Preparation Example 10: The difference from Preparation Example 7 is that the VA content of the EVA resin is 18%.
[0042] Preparation Example 11: The difference from Preparation Example 7 is that the carbon nanotube dispersion is prepared by mixing polyethersulfone-modified carbon nanotubes and polyimide emulsion in a mass ratio of 1:1 and then ultrasonicating for 30 minutes, and the polyethersulfone-modified carbon nanotubes are prepared by Preparation Example I.
[0043] Preparation Example 12: The difference from Preparation Example 7 is that the carbon nanotube dispersion is prepared by mixing polyethersulfone-modified carbon nanotubes and polyimide emulsion in a mass ratio of 1:0.5 and then ultrasonicating for 30 minutes, and the polyethersulfone-modified carbon nanotubes are prepared by Preparation Example I.
[0044] Preparation Example 13: The difference from Preparation Example 11 is that an equal amount of multi-walled carbon nanotubes is used to replace the polyethersulfone modified carbon nanotubes.
[0045] Preparation Example 14: The difference from Preparation Example 11 is that an equal amount of a mixed solution of DMF and deionized water in a volume ratio of 1:4 is used to replace the polyimide emulsion. Example
[0046] Example 1: A high resilience sole material, the raw material dosage is shown in Table 1, wherein the VA content in the EVA resin is 21%, selected from Taiwan Plastics, China, model 7360M, the foaming agent is AC foaming agent (azodicarbonamide), the crosslinking agent is diisopropylbenzene peroxide, the inorganic filler is carbon nanotubes, the cell stabilizer is zinc oxide, and the polytetrafluoroethylene microporous fiber is prepared as follows: 3g of polyethylene oxide is dissolved in distilled water to prepare a polyethylene oxide solution with a concentration of 4wt%, and 166g of a solid content of 60 wt% polytetrafluoroethylene emulsion, stirred for 4h to obtain a uniform spinning solution, electrospun to obtain nanofibers, vacuum dried at 40℃ for 12h, sintered at 400℃ in a muffle furnace for 10min, the mass ratio of polyethylene oxide to polytetrafluoroethylene was 0.03:1, the positive voltage of the spinning was 9kV, the negative voltage was 1kV, the receiving distance was 20cm, the spinning speed was 0.25ml / h, the polytetrafluoroethylene emulsion was selected from Chemours, USA, the model was DISP30, the molecular weight of PEO was 5×10 6 g / mol, the highly elastic particles include a TPU layer, a mixed layer and a TPU layer in contact with each other, the TPU layer is made by casting a TPU solution, the mixed layer is made by casting a mixed liquid made of left-handed polylactic acid and modified graphene oxide in a mass ratio of 1:0.05, the mass ratio of the casting amount of TPU solution to the casting amount of the mixed liquid in a single TPU layer is 1:0.8, and the highly elastic particles are made by Preparation Example 1.
[0047] The method for preparing the high-resilience sole material comprises the following steps: S1, mixing EVA matrix resin, stearic acid, inorganic filler, cell stabilizer, polytetrafluoroethylene microporous fiber and high elastic particles, and kneading at 125° C. for 10 minutes to prepare a premix; S2. The premix is mixed with a foaming agent and a cross-linking agent, kneaded at 110° C. for 10 min, and then granulated at 120° C. to obtain pellets, which are injected into a mold at an injection temperature of 140° C. and a mold temperature of 175° C.
[0048] Table 1 Amount of raw materials for high resilience sole materials in Examples 1-5 Embodiment 2: A high resilience sole material, the raw material dosage is as shown in Table 1, wherein the VA content in the EVA resin is 21%, selected from Taiwan Plastics, China, model 7360M, the foaming agent is AC foaming agent (azodicarbonamide), the crosslinking agent is diisopropylbenzene peroxide, the inorganic filler is carbon nanotubes, the cell stabilizer is zinc oxide, and the preparation method of polytetrafluoroethylene microporous fiber is as follows: 5g of polyethylene oxide is dissolved in distilled water to prepare a polyethylene oxide solution with a concentration of 4wt%, and 166.7g of solid content is added. 60wt% polytetrafluoroethylene emulsion was stirred for 4h to obtain a uniform spinning solution, electrospun to obtain nanofibers, vacuum dried at 40℃ for 12h, and sintered in a muffle furnace at 420℃ for 5min. The mass ratio of polyethylene oxide to polytetrafluoroethylene was 0.05:1, the positive voltage of the spinning voltage was 9kV, the negative voltage was 1kV, the receiving distance was 20cm, and the spinning speed was 0.25ml / h. The polytetrafluoroethylene emulsion was selected from Chemours, USA, model DISP30, and the molecular weight of PEO was 5×10 6 g / mol, the highly elastic particles include a TPU layer, a mixed layer and a TPU layer in contact with each other, the TPU layer is made by casting a TPU solution, the mixed layer is made by casting a mixed liquid made of left-handed polylactic acid and modified graphene oxide in a mass ratio of 1:0.03, the mass ratio of the casting amount of TPU solution to the casting amount of the mixed liquid in a single TPU layer is 1:0.6, and the highly elastic particles are made by Preparation Example 2.
[0049] The method for preparing the high-resilience sole material comprises the following steps: S1, mixing EVA matrix resin, stearic acid, inorganic filler, cell stabilizer, polytetrafluoroethylene microporous fiber and high elastic particles, and kneading at 115° C. for 15 minutes to prepare a premix; S2. The premix is mixed with a foaming agent and a cross-linking agent, kneaded at 100° C. for 5 min, and then granulated at 110° C. to obtain pellets, which are injected into a mold at an injection temperature of 110° C. and a mold temperature of 175° C.
[0050] Example 3-5: A high-elastic sole material, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 1.
[0051] Example 6: A high-elastic sole material, which is different from Example 1 in that the high-elastic particles are made from Preparation Example 6.
[0052] Example 7: A high-elastic sole material. The difference from Example 6 is that the inorganic filler is carbon nanotube / PCL composite fiber, and the carbon nanotube / PCL composite fiber is made by Preparation Example 7.
[0053] Example 8: A high-elastic sole material. The difference from Example 6 is that the inorganic filler is carbon nanotube / PCL composite fiber, and the carbon nanotube / PCL composite fiber is made by Preparation Example 8.
[0054] Example 9: A high-elastic sole material. The difference from Example 7 is that the inorganic filler is carbon nanotube / PCL composite fiber, and the carbon nanotube / PCL composite fiber is made by Preparation Example 9.
[0055] Example 10: A high-elastic sole material, which differs from Example 7 in that the inorganic filler is carbon nanotube / PCL composite fiber, and the carbon nanotube / PCL composite fiber is made from Preparation Example 10.
[0056] Example 11: A high-elastic sole material. The difference from Example 7 is that the inorganic filler is carbon nanotube / PCL composite fiber, and the carbon nanotube / PCL composite fiber is made by Preparation Example 11.
[0057] Example 12: A high-elastic sole material. The difference from Example 7 is that the inorganic filler is carbon nanotube / PCL composite fiber, and the carbon nanotube / PCL composite fiber is made by Preparation Example 12.
[0058] Example 13: A high-elastic sole material, which is different from Example 11 in that the inorganic filler is carbon nanotube / PCL composite fiber, and the carbon nanotube / PCL composite fiber is made by Preparation Example 13.
[0059] Example 14: A high-elastic sole material, which is different from Example 11 in that the inorganic filler is carbon nanotube / PCL composite fiber, and the carbon nanotube / PCL composite fiber is made by Preparation Example 14.
[0060] Comparative Example Comparative Example 1: A high-rebound sole material, which is different from Example 1 in that the high-elastic particles are made from Preparation Example 3.
[0061] Comparative Example 2: A high-rebound sole material, which is different from Example 1 in that the high-elastic particles are made from Preparation Example 4.
[0062] Comparative Example 3: A high-rebound sole material, which is different from Example 1 in that the high-elastic particles are made from Preparation Example 5.
[0063] Comparative Example 4: A high-resilience sole material, which differs from Example 1 in that no high-elastic particles are added.
[0064] Comparative Example 5: A high-resilience sole material, which differs from Example 1 in that polytetrafluoroethylene microporous fibers are not added.
[0065] Performance testing The sole material was prepared according to the methods in the examples and comparative examples, and the performance was tested according to the following methods. The test results are recorded in Table 2.
[0066] 1. Tensile strength: Tested in accordance with GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".
[0067] 2. Resilience: Test in accordance with GB / T6670-2008 "Determination of the rebound properties of soft foam polymer materials by the falling ball method".
[0068] 3. Abrasion resistance: Test in accordance with GB / T9867-2008 "Determination of abrasion resistance of vulcanized rubber or thermoplastic rubber".
[0069] 4. Elastic recovery rate: The elastic recovery rate is the recovery rate under 100% elongation. The dumbbell-shaped sample is stretched at a speed of 10mm / min under the clamp until its gauge length is twice the original, then released and allowed to recover for 5 minutes in a natural state, and then the length between the sample gauge lines is measured. The elastic recovery rate R is calculated by the following formula: R = (2L0-L)l0 / L0, where L0 is the gauge length and L is the distance between the sample gauge lines after the external force is removed for 5 minutes.
[0070] 5. Compression permanent deformation: Test according to HG / T-2009 "Compression deformation test method for microporous materials of rubber shoes".
[0071] Table 2 Performance test results of high rebound sole materials Combining Examples 1-5 and the data in Table 2, it can be seen that in Examples 1-5, specific high-elastic particles are used, polytetrafluoroethylene microporous fibers are added, and carbon nanotubes are used as inorganic fillers. The high-rebound sole materials made in this way have high tensile strength, large rebound rate and high elastic recovery rate, and the compression permanent deformation is less than 32%. It has good shape recovery ability and is not easy to produce permanent deformation.
[0072] Compared with Example 1, Example 6 uses the high-elastic particles prepared in Preparation Example 6, and the modified graphene oxide is reduced-modified graphene oxide grafted with polycaprolactone. It can be seen from the data in Table 2 that the tensile strength of the sole material prepared in Example 6 is increased, the elastic recovery rate is increased, the compression permanent deformation is reduced, and the deformation amount is reduced.
[0073] Compared with Example 6, Examples 7 and 8 use the carbon nanotube / PCL composite fibers prepared in Preparation Examples 7 and 8, respectively. It can be seen that the sole materials prepared in Examples 7 and 8 have increased tensile resistance, wear resistance and resilience, enhanced elastic recovery, and improved deformation resistance.
[0074] In Example 9, the carbon nanotube / PCL composite fiber prepared in Preparation Example 9 was used. Compared with Example 7, EVA and PCL were not irradiated and modified. It can be seen that the tensile strength of the sole material is reduced, the rebound rate does not change much, the elastic recovery rate is reduced, and deformation is easy to occur.
[0075] In Example 10, the carbon nanotube / PCL composite fiber prepared in Preparation Example 10 was used. Compared with Example 7, the tensile strength was increased and the wear resistance was enhanced, but the elastic recovery rate was reduced, and the content of EVA resin was reduced. It can be seen that the inorganic filler made of EVA resin with a high VA content can eliminate residual strain and improve the self-repair function of the sole material.
[0076] Compared with Example 7, Examples 11 and 12 use polyethersulfone modified carbon nanotubes and polyimide emulsion to prepare carbon nanotube dispersions. Table 2 shows that the wear resistance of the sole materials prepared in Examples 11 and 12 is significantly enhanced, and the tensile resistance is slightly improved.
[0077] Example 13 and Example 14 used the carbon nanotube / PCL composite fibers prepared in Preparation Example 14 and Preparation Example 14, respectively. Unmodified multi-walled carbon nanotubes were used in Example 13, and polyimide emulsion was not used in Example 14. Table 2 shows that the wear resistance of the sole materials prepared in Example 13 and Example 14 decreased, and the tensile strength was weakened.
[0078] In Comparative Example 1, the highly elastic particles prepared in Preparation Example 3 were used. Compared with Example 1, no modified graphene oxide was added to the mixed solution. The dispersibility of graphene oxide in the solution made of left-handed polylactic acid was reduced. The data in Table 2 showed that the tensile strength of the sole material was reduced, the elastic recovery rate was reduced, and the shape recovery ability was deteriorated.
[0079] Compared with Example 1, Comparative Example 2 uses the highly elastic particles prepared in Preparation Example 4. The highly elastic particles are made of a mixed layer, a TPU layer and a mixed layer. As can be seen from Table 2, the elastic recovery rate of the sole material prepared in Comparative Example 2 is reduced, indicating that the elasticity of TPU is not sufficient to restore the shape of L-polylactic acid.
[0080] In Comparative Example 3, the highly elastic particles prepared in Preparation Example 5 were used. Compared with Example 1, only one TPU layer was crushed to obtain the particles. It can be seen that the mechanical strength of the sole material decreased, the shape recovery performance decreased, and the deformation amount increased.
[0081] Compared with Example 1, Comparative Example 4 did not add high-elastic particles, and the tensile strength, wear resistance and elastic recovery effects of the sole material were reduced.
[0082] In Comparative Example 5, no polytetrafluoroethylene microporous fiber is added. Compared with Example 1, its wear resistance is weakened, its anti-tensile effect is worse, and its elastic recovery rate is reduced.
[0083] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-resilience sole material, characterized in that: The raw materials include the following parts by weight: 100 parts of EVA base resin, 1-3 parts of stearic acid, 8-12 parts of foaming agent, 5-10 parts of cross-linking agent, 10-20 parts of inorganic filler, 5-10 parts of cell stabilizer, 5-10 parts of polytetrafluoroethylene microporous fiber, and 10-15 parts of high-elastic particles; The highly elastic particles include a TPU layer, a mixed layer and a TPU layer in contact with each other, the TPU layer is cast by a TPU solution, the mixed layer is cast by a mixed solution formed by left-handed polylactic acid and modified graphene oxide, the mass ratio of left-handed polylactic acid to modified graphene oxide in the mixed solution is 1:0.03-0.05, and the mass ratio of the casting amount of TPU solution to the casting amount of the mixed solution in a single TPU layer is 1:0.6-0.
8.
2. The high resilience sole material according to claim 1, characterized in that: The preparation method of the high elastic particles is as follows: Dissolving a thermoplastic polyurethane elastomer to prepare a TPU solution having a concentration of 10-12 wt %; Dissolve L-polylactic acid to obtain a solution with a concentration of 15-18 wt%, add modified graphene oxide, heat to 80-90° C., stir evenly, and obtain a mixed solution; The TPU solution is poured into a mold, vacuum dried to obtain a TPU layer, the mixed liquid is poured on the TPU layer, vacuum dried to form a mixed layer, and the TPU solution is poured on the mixed layer, vacuum dried to form a TPU layer, hot pressed into thin sheets, and crushed to obtain high-elastic particles.
3. The high resilience sole material according to claim 2, characterized in that: The modified graphene oxide is reduced modified graphene oxide grafted with polycaprolactone.
4. The high resilience sole material according to claim 1, characterized in that: The polytetrafluoroethylene microporous fiber is prepared by mixing a polyethylene oxide solution and a polytetrafluoroethylene emulsion, electrostatically spinning, and sintering at 400-420° C. for 5-10 minutes. The mass ratio of polyethylene oxide to polytetrafluoroethylene is 0.03-0.05:
1.
5. The high resilience sole material according to claim 1, characterized in that: The inorganic filler is carbon nanotube / PCL composite fiber.
6. The high resilience sole material according to claim 5, characterized in that: The preparation method of the carbon nanotube / PCL composite fiber is as follows: EVA resin and PCL resin were mixed in a mass ratio of 0.2-0.3:1 and melted. 60 The fiber matrix is prepared by irradiating with a Co source at a dose of 100-200 kGy and then melt extruding. The fiber matrix is placed in a xylene solution at 40-50° C., soaked for 30-40 minutes, then added into a carbon nanotube dispersion, ultrasonicated, filtered, washed and dried.
7. The high resilience sole material according to claim 6, characterized in that: The carbon nanotube dispersion comprises polyethersulfone modified carbon nanotubes and polyimide emulsion in a mass ratio of 1:0.5-1.
8. The high resilience sole material according to claim 6, characterized in that: The VA content of the EVA resin is 28-33wt%.
9. The high resilience sole material according to claim 1, characterized in that: The foaming agent is AC foaming agent; the cross-linking agent is dicumyl peroxide; The cell stabilizer is selected from at least one of zinc oxide, zinc stearate, magnesium stearate and zinc carbonate.
10. The method for preparing the high resilience sole material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The EVA matrix resin, stearic acid, inorganic filler, cell stabilizer, polytetrafluoroethylene microporous fiber and high elastic particles are mixed and kneaded at 115-125° C. for 10-15 minutes to prepare a premix; The premix is mixed with a foaming agent and a cross-linking agent, kneaded at 100-110°C for 5-10 minutes, and then granulated to obtain pellets, which are injected into a mold at an injection temperature of 110-140°C.
Citation Information
Patent Citations
High-resilience and wear-resistant sole material and preparation method thereof
CN111607156A
Cited By
Vibration-triggered self-lubricating plastic, circular weaving machine plastic friction wheel and manufacturing process of vibration-triggered self-lubricating plastic and circular weaving machine plastic friction wheel
CN121779917A